The wrong family [compact disc, unabridged] - Fisher, Tarryn (Harlequin Audio, 2020)
Juno was wrong about Winnie Crouch. Before moving in with the Crouch family, Juno thought Winnie and her husband, Nigel, had the perfect marriage, the perfect son--the perfect life. Only now that she's living in their beautiful house, she sees the cracks in the crumbling facade are too deep to ignore. Still, she isn't one to judge. After her grim diagnosis, the retired therapist simply wants a place to live out the rest of her days in peace. But that peace is shattered, the day Juno overhears a chilling conversation between Winnie and Nigel. She shouldn't get involved. She really shouldn't. But this could be her chance to make a few things right.